2021
DOI: 10.1097/md.0000000000028259
|View full text |Cite
|
Sign up to set email alerts
|

Severe re-expansion pulmonary edema after chest tube insertion for the treatment of spontaneous pneumothorax

Abstract: Rationale: Re-expansion pulmonary edema (REPE) is a rare complication after chest tube insertion for the treatment of spontaneous pneumothorax. However, this complication can be life threatening when it occurs. Therefore, it is necessary to recognize REPE early and treat it appropriately. In the present study, we report a severe REPE case occurring after chest tube insertion in a patient with spontaneous pneumothorax. Patient concerns: A 27-year-old male patient visited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…The recommended clinical management is supportive care consisting of non-invasive positive-pressure ventilation, as well as mechanical ventilation, if necessary. Coughing may be the initial symptom 2. Stopping drainage immediately may have been an option for suppressing the progression of oedema in the present patient.…”
Section: Descriptionmentioning
confidence: 76%
See 1 more Smart Citation
“…The recommended clinical management is supportive care consisting of non-invasive positive-pressure ventilation, as well as mechanical ventilation, if necessary. Coughing may be the initial symptom 2. Stopping drainage immediately may have been an option for suppressing the progression of oedema in the present patient.…”
Section: Descriptionmentioning
confidence: 76%
“…Its incidence ranges from 0.9% to 14.4% in patients with spontaneous pneumothorax undergoing drainage. The risk factors of REPE include longer duration and greater extent of lung collapse, young age and rapid lung expansion 1 2. One recent study reported an incidence of 21.6% in patients with a lung collapse duration longer than 4 days and severe lung collapse.…”
Section: Descriptionmentioning
confidence: 99%
“…Patients with unilateral pulmonary edema may benefit from lying on the unaffected side to improve intrapulmonary shunt. 27 , 28 There are no specific medication guidelines for RPE. Some evidence suggests that the use of diuretics, steroids, and inotropes may be considered based on clinical indications.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha descrito una incidencia entre 0,9 y 20 % por todas las causas de edema pulmonar y menor al 1 % tras una toracostomía cerrada 4 , con una relación de hombres a mujeres de 38:9 y una mayor prevalencia en la segunda y tercera décadas de la vida, pues las personas de mayor edad presentan cambios en la mecánica pulmonar y características de la barrera alveolo-capilar secundarios al envejecimiento que funcionan como un factor protector para el EPR [4][5][6] .…”
Section: Discussionunclassified
“…Adicionalmente, los vasos sanguíneos se adaptan al colapso pulmonar crónico y la hipoxia prolongada y, debido a sus cambios histológicos, son vulnerables a la tracción. La reexpansión y la reperfusión del pulmón isquémico aumenta los radicales libres de oxígeno, que conduce a daño endotelial vascular directo [4][5][6][7] . Si bien, por lo general, el EPR ocurre en el mismo pulmón inicialmente colapsado, se han descrito casos en los que ocurre bilateral o incluso contralateral [7][8][9] , por lo que en la patogénesis del EPR también se ha descrito el rol de sustancias vasoactivas como histamina, prostaglandina o factores neurogénicos 6,7 .…”
Section: Discussionunclassified